Designing and implementing more effective Integrated Early Warning Systems in mountain areas: a case study from Northern Italy - Carolina García (Revue de Géographie Alpine)
It is essential to consider and to understand the social context in which an Early Warning System (EWS) is planned and to integrate all of its components, otherwise it is likely to fail. EWS are complex tools for disaster risk reduction which are only effective if they generate an appropriate response in the exposed population. Any effective EWS relies on the reaction capacity of all stakeholders. This reaction capacity is strongly dependent on how well EWS are integrated within their social context, especially with regards to potential marginalized and vulnerable communities. This dependence was confirmed in the study area in Valtellina di Tirano, northern Italy, which is recurrently affected by multiple mountain hazards. The local population is geographically marginalized due to restricted access to the region and exposure to hazardous events, and socially marginalized due to the lack of participation in decision making. Results of a survey show that the local population has low levels of perceived risk, a general lack of self-responsibility with regard to disaster risk reduction, and a tendency to transfer the responsibility to the authorities. However, respondents acknowledge and show interest in addressing their lack of preparedness and in participating actively in disaster risk reduction efforts. A follow-up survey demonstrates that significant variations in vulnerability within a given community over time, occur together with changes in traditional livelihood activities, economic systems and population demographics.